Spontaneous Ventral Spinal Epidural Hematoma in an Infant: An Unusual Presentation - ABBAS, Asad; AFZAL, Kamran; MUJEEB, Athar A.; SHAHAB, Tabassum; KHALID, Mohd. (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Abbad A, Afzal K, Mujeeb AA, Shahab T, Khalid M. Spontaneous Ventral Spinal Epidural Hematoma in an Infant: An Unusual Presentation. Iran J Child Neurol. 2013 Spring;7(2):47-50. Abstract Spontaneous ventral spinal epidural hematomas are extremely rare in children and clinically recognized by the appearance of acute asymmetric focal motor and sensory involvement. In infants, the initial presenting symptoms are very non-specific and irritability is often the only initial manifestation. Appearance of other neurological signs may be delayed up to hours or even days later. In the absence of significant precipitating factors such as severe trauma or previously known coagulopathies, the diagnosis is usually delayed until the full picture of severe cord compression is developed. The diagnosis is finally made by performing magnetic resonance imaging. We report a 5-month-old infant with spinal epidural hematoma who presented with symmetrical upper limb weakness and diaphragmatic involvement to highlight the importance of recognizing the atypical manifestations for early diagnosis and intervention. References: 1. Phillips TW, Kling TF Jr, McGillicuddy JE. Spontaneous ventral spinal epidural hematoma with anterior cord syndrome: report of a case. Neurosurgery 1981;9:440-3. 2. Patel H, Boaz JC, Phillips JP, Garg BP. Spontaneous spinal epidural hematoma in children. Pediatr Neurol 1998;19:302-7. Review. 3. Penar PL, Fischer DK, Goodrich I, Bloomgarden GM, Robinson F. Spontaneous spinal epidural hematoma. Int Surg 1987;72:218-21. 4. Noth I, Hutter JJ, Meltzer PS, Damiano ML, Carter LP. Spinal epidural hematoma in a hemophilic infant. Am J Pediatr Hematol Oncol 1993;15:131-4. Review. 5. Beatty RM, Winston KR. Spontaneous cervical epidural hematoma. A consideration of etiology. J Neurosurg 1984;61:143-8. 6. Alva NS. Traumatic spinal epidural hematoma of a 10-month-old male: a clinical note. Pediatr Neurol 2000;23:88-9. Review. 7. Aminoff MJ: Vascular disorders of the spinal cord, in Davidoff RA (ed): Handbook of the Spinal Cord. Infections and Cancer, Vol 5. New York: Marcel Dekker, 1986, pp 271-273. 8. Blount J, Doughty K, Tubbs RS, Wellons JC, Reddy A, Law C, et al. In utero spontaneous cervical thoracic epidural hematoma imitating spinal cord birth injury. Pediatr Neurosurg 2004;40:23-7. 9. Iguchi T, Ito Y, Asai M, Ito J, Okada N, Murakami M. [A case of spontaneous spinal epidural hematoma]. No To Hattatsu 1993;25:267-70. Review. Japanese. 10. Nagel MA, Taff IP, Cantos EL, Patel MP, Maytal J, Berman D. Spontaneous spinal epidural hematoma in a 7-year-old girl. Diagnostic value of magnetic resonance imaging. Clin Neurol Neurosurg 1989;91:157-60. 11. Metzger G, Singbartl G. Spinal epidural hematoma following epidural anesthesia versus spontaneous spinal subdural hematoma. Two case reports. Acta Anaesthesiol Scand 1991;35:105-7. 12. Patel H, Garg BP. Increasing irritability with sudden onset of flaccid weakness. Semin Pediatr Neurol 1996;3:192-7. 13. Tewari MK, Tripathi LN, Mathuriya SN, Khandelwal N, Kak VK. Spontaneous spinal extradural hematoma in children. Report of three cases and a review of the literature. Childs Nerv Syst 1992;8:53-5. Review. 14. Pecha MD, Able AC, Barber DB, Willingham AC. Outcome after spontaneous spinal epidural hematoma in children: case report and review of the literature. Arch Phys Med Rehabil 1998;79:460-3. Review.